The fate of Uganda’s Northern white rhino translocated to Murchison Falls National Park in 1961 and 1964 - Roger Wheater; Ian Parker (Pachyderm)
This historical note records the demise of Uganda’s northern white rhino (Ceratotherium simum cottoni) population for the scientific record. Ceratotherium simum was distributed in Africa between the Mahgreb and the southern Cape, wherever there was suitable grazing (though not necessarily in all places at the same time), until after the appearance of Homo sapiens on the continent. By the eighteenth century this extensive range had contracted into two widely separated and taxonomically distinct populations, one Sudanic and the other southern African. The Sudanic population of northern white rhino (NWR) were scientifically recognised in 1907 as (Ceratotherium simum cottoni) taxonomically separate from C.s.simum. The NWR previously occurred in Uganda but is currently believed to be extinct in the country. Given low human densities and the inaccessibility of much of the Central African Republic and Southern Sudan, it is possible that a few undetected individuals still exist in remote places. For example, while extinct in the Democratic Republic of the Congo’s Garamba National Park, a few may possibly remain in the contiguous ‘domain de chasse’.